PEMANFAATAN LIMBAH TEMPURUNG KELAPA MENJADI BRIKET ARANG SEBAGAI BAHAN BAKAR ALTERNATIF DI DESA KAMARIAN KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - H. Makaruku, Marlita; L. Tanasale, Vilma; Goo, Nureny (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
Kamarian Village is one of the coconut producing villages in Kairatu District which manages coconut plantations with high yields. The coconut fruit processing industry is generally still focused on processing fruit flesh as the main product. By-products such as leaves, roots, stems, and coconut shells are often neglected and disposed of as waste, causing environmental pollution. One effort that can be made to take advantage of this problem is through processing coconut shell waste into briquettes. The purpose of making briquettes from coconut shells is to reduce agricultural waste in the form of coconut shells so that wasted coconut shell waste can be reduced by making coconut shell briquettes. This community service activity is carried out through the following stages: preparation, lectures and discussions, training in making briquettes, as well as monitoring and evaluation. The results obtained from the implementation of this PKM activity are that the community gains new knowledge on how to utilize coconut shell waste into briquettes which can be used as alternative fuels and can increase income for the community.